(untitled) (Indian Journal of Animal Production and Management, 2024)
An investigation was undertaken to study knowledge level of women dairy farmers on dairy animal management in Guntur district of Andhra Pradesh. A total of 225 randomly selected women dairy farmers in three animal husbandry divisions of Guntur district in Andhra Pradesh viz., Pedaravuru, Guntur and Narasaraopeta. The farm women in the study area had good knowledge regarding importance of Artificial Insemination (96.40%), followed by identifying the animals in estrus (95.10%), importance of treatment of anestrus and repeat breeding animals (92.90%), culling of unproductive animals (87.10%) and pregnancy diagnosis at 3 months after insemination (86.70%). Poor knowledge was observed regarding dry period (20.90%), feeding concentrates according to the level of production (16.00%), strip cup test to detect mastitis (13.78%), urea treatment of paddy straw (4.90%) and practicing of dry cow therapy (4.89%) in the study area.